Economic Evaluation of Fluticasone Propionate/Formoterol (Flutiform®) vs. Fluticasone/Salmeterol and Budesonide/Formoterol in Spain. Issue 2 (December 2016) - Moragón, Eva; Delgado, Julio; Ojeda, Pedro; Llano, Luis; Collar, Juan; Antón-Rodriguez, Cristina; Martín-Saborido, Carlos
Abstract Introduction The aim of this economic evaluation was to estimate the cost-effectiveness of fluticasone propionate/formoterol (FP/FORM; Flutiform® ) and compare it to those of fluticasone/salmeterol (FS) and budesonide/formoterol (BF) when used in the treatment of adult patients with moderate-to-severe asthma. Methods A Markov model was developed with five asthma health states: successful control, suboptimal control, outpatient-managed exacerbation, inpatient-managed exacerbation, and death. The time horizon was set at 12 months. Transition probabilities and indirect resource utilization were derived from previous international and Spanish publications. Univariate and probabilistic sensitivity analyses (SAs) were applied. Results FP/FORM was less expensive to acquire than FS or BF (20% lower than FS and 30% lower than BF), while the quality-adjusted life years (QALYs) of the three options compared were very similar. Cost per patient in the FP/FORM cohort was 9326€/year, making it the cheapest option, 1.5% cheaper than FS and 2.6% cheaper than BF. The suboptimal control health state dominated the costs (80% of the total cost) in each of the analyzed options and scenarios. The results of the SAs verified the data obtained from the base case scenario. Conclusions From a Spanish societal perspective, in 2014, FP/FORM produced a similar gain in QALYs but at a lower cost when compared to FS and BF in a highly meaningful number of replications and scenarios. FP/FORM can therefore be considered a cost-effective option in the treatment of moderate-to-severe asthma in Spain. The cost savings were mainly due to the significantly lower acquisition cost of FP/FORM than the other two options. Funding Mundipharma Pharmaceuticals, S.L., Madrid, Spain.